The Relationship Between Al-Quran Recitation Frequency and Elderly’s Memory Retention in Lhok Bengkuang Village of Tapaktuan District, South Aceh - Alkairi, Jundillah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2023)
Reciting Al-Quran has become part of Muslim daily practices as a form of worship not only to obtain rewards and to seek tranquility through dzikr (remembering God) but also to comprehend its meanings. The routines of reading the Al-Quran have been done by various groups of age including elderly women in Al-Munawwarah mosque who also learn tahsin (Quranic recitation) diligently to read the Al-Quran properly. This study aims to investigate the relationship between Al-Quran recitation routines and memory retention of elderly women in Al-Munawwarah mosque in Lhok Bengkuang village, Tapaktuan district. The researchers used a quantitative approach to conduct this study with field research as a means to collect data. This data collection was conducted by distributing questionnaires to the respondents of the selected sample. Then the data were analyzed by using SPSS to examine the correlation or level of significant relationship between Al-Quran recitation frequency and elderly women’s memory retention. The results of the study show that a significant interrelationship or inferential correlation value of 0.008, with a coefficient correlation value of 0.710 was obtained. The value was less than alpha (0.05), thus, it can be concluded that there is a significant relationship between the routines of reading the Al-Quran and cognitive function.